2019
DOI: 10.1002/hed.25727
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of interstitial lung disease of patients with head and neck cancer treated with cetuximab

Abstract: Background Interstitial lung disease (ILD) is known as a potentially severe adverse event associated with epidermal growth factor receptor (EGFR)‐targeted therapy. The incidence and risk factors of ILD in patients with head and neck squamous cancer (HNSCC) treated with cetuximab, an anti‐EGFR monoclonal antibody, have not been established. Methods We retrospectively reviewed patients with HNSCC who received cetuximab from December 2012 to December 2016 at our institute and evaluated the incidence and risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Many factors can damage AECs, such as preexisting pulmonary diseases, including chronic obstructive pulmonary disease (COPD), asthma and pleural effusion [32], and some anticancer treatments, such as chemotherapy [42], targeted therapy [43] and radiotherapy [44]. In this study, we found that smoking history and pleural effusion were associated with CIP, while smoking history was an independent risk factor for CIP.…”
Section: Discussionmentioning
confidence: 75%
“…Many factors can damage AECs, such as preexisting pulmonary diseases, including chronic obstructive pulmonary disease (COPD), asthma and pleural effusion [32], and some anticancer treatments, such as chemotherapy [42], targeted therapy [43] and radiotherapy [44]. In this study, we found that smoking history and pleural effusion were associated with CIP, while smoking history was an independent risk factor for CIP.…”
Section: Discussionmentioning
confidence: 75%
“…The DILD toxicity of cetuximab might be dose-dependent, and the biweekly regimen is now approved for use, but the concerns over the development of DILD should remain. [3,5–8]…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study of patients with head and neck tumors, the incidence of interstitial pneumonia during cetuximab treatment was 4.5% (9/201), of which 8 cases were grade 3 or higher. High salivation liquefaction sugar chain antigen-6 and smoking history may be risk factors for interstitial pneumonia in patients with head and neck tumors [16].…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature reports on interstitial pneumonia caused by cetuximab [11][12][13][14][15][16], there is no certain trend in the onset time of interstitial pneumonia caused by cetuximab. A Japanese study has reported that the incidence of cetuximab-related lung injury occurring in patients with metastatic colorectal cancer was 1.2% (24/2006), the incidence of grade 3 or higher was 0.7% (15/2006) and the median time of onset was 101 days (17-431 days).…”
Section: Discussionmentioning
confidence: 99%